PENGARUH SARANA DAN PRASARANA KAMPUS TERHADAP SUASANA AKADEMIK MAHASISWA PERGURUAN TINGGI - Paskalis Simon Kewisa Lein; Emanuel I. D. Je’e Maly; Graciana Amanda Bele (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to empirically examine the effect of campus infrastructure and facilities on the academic atmosphere of higher education students in Kupang City, East Nusa Tenggara. The primary research question is formulated into one central focus: How significantly do educational infrastructure and facilities influence the development of a conducive academic atmosphere within the campus environment? A quantitative approach with an explanatory survey method was employed. The research population comprised active students from three higher education institutions in Kayu Putih, Kupang City: STIPAS Archdiocesan of Kupang, Muhammadiyah University of Kupang, and Citra Bangsa University. The results reveal that the availability, quality, and accessibility of educational infrastructure exert a positive and significant impact of 64.5% on the academic atmosphere. Therefore, reinforcing physical components like classroom environments, advanced laboratories, libraries, and high-speed internet access serves as a fundamental pillar to promote academic freedom, student creativity, and cognitive advancement across higher education institutions in Kupang.